2022
DOI: 10.1186/s12889-022-14695-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between e-health literacy and chronic disease self-management in older Chinese patients with chronic non-communicable diseases: a mediation analysis

Abstract: Background Chronic non-communicable diseases (CNCDs) are an urgent public health issue in China, especially among older adults. Hence, self-management is crucial for disease progression and treatment. Electronic health (e-health) literacy and self-efficacy positively correlate with self-management. However, we know little about their underlying mechanisms in older adults with CNCDs. Objective To explore the factors that influence chronic disease se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In other words, self-efficacy mediates the relationship between eHealth literacy and diabetes self-management. This finding is congruent with the findings of a previous study on patients with chronic disease (Wu et al, 2022). A systemic review conducted by Xie et al (2022) emphasized the need for further exploration and elucidation of the various potential mediators of the relationship between eHealth literacy and health-related outcomes (including self-management).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, self-efficacy mediates the relationship between eHealth literacy and diabetes self-management. This finding is congruent with the findings of a previous study on patients with chronic disease (Wu et al, 2022). A systemic review conducted by Xie et al (2022) emphasized the need for further exploration and elucidation of the various potential mediators of the relationship between eHealth literacy and health-related outcomes (including self-management).…”
Section: Discussionmentioning
confidence: 99%
“…To monitor SMS, focus group participants emphasise the use of practical tools and devices. Although this can be very useful, it is important to approach it cautiously (32,33), especially since several support techniques require digital skills from patients (34). In addition, the use of questionnaires to guide this dynamic process is well-described in literature and was also mentioned by the focus group participants (35,36).…”
Section: Comparison With Literaturementioning
confidence: 99%
“…In China, the self-management of elderly patients with chronic diseases is still at a low level [8]. Most elderly people have limited knowledge of diseases, and their poor management may lead to additional complications and medical expenses, and at the same time have a certain impact on their quality of life [9]. Studies have shown that self-management of chronic diseases can improve the health status and quality of life of elderly patients with chronic diseases and reduce the incidence of complications [10].…”
Section: Introductionmentioning
confidence: 99%